Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
what you can do is multiply the whole first equation by 12, so 6x + 26.4y = 108.
then since the coefficients of the x value (the number in front of the x) are the same in both equations, you can subtract the second equation from the first:
6x + 26.4y = 108
-(6x + 0.4y = -22)
26y = 130 divide by 26
y = 5
you can then plug y=5 into one of the equations to solve for x:
0.5x + 2.2(5) = 9
0.5x + 11 = 9 subtract 11 from both sides
0.5x = -2 multiply each side by 2
x = -4
then since the coefficients of the x value (the number in front of the x) are the same in both equations, you can subtract the second equation from the first:
6x + 26.4y = 108
-(6x + 0.4y = -22)
26y = 130 divide by 26
y = 5
you can then plug y=5 into one of the equations to solve for x:
0.5x + 2.2(5) = 9
0.5x + 11 = 9 subtract 11 from both sides
0.5x = -2 multiply each side by 2
x = -4
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.